EFFECTS OF LITHIUM NANO-SCALED PARTICLES ON LOCAL AND SYSTEMIC STRUCTURAL AND FUNCTIONAL ORGANISM TRANSFORMATIONS UNDER TUMOUR GROWTH - PRO. AKOM PEMMANUEL NUJOR, AKOM PEMMANUEL NUJOR; KOSOMKO, ABUOH RIDELIS (International Journal of Multidisciplinary Research and Studies, 2021)
The results of a study of structural and metabolic changes in CBA mice with malignant hepatoma caused by carbonate Nano-sized particles are presented. Light microscopy, microscopy and other biochemical methods were accustomed to showing that injection of antipsychotic Nano-sized particles to the periphery of the tumour ends up in enhanced destructive processes within the tumour. the number of neutrophils and macrophages within the tumour increased, whereas the density of blood vessels and haemoglobin concentration were reduced; the extent of tumour necrosis lipid peroxidation and production of gas was also increased. At the identical time, the activity of antioxidant enzymes including SOD and catalase remained identical. The introduction of antipsychotic Nano-scaled particles protects vital organs including the guts and lungs from the damaging effect of secondary products of lipid peroxidation.